Understanding Households' Willingness to Pay for Improved Sanitation Services in Benin: A Study Protocol - Nicolas Gaffan; Alphonse Kpozehouen; Cyriaque Degbey; Yolaine Glele Ahanhanzo; Moussiliou Noël Paraïso (SAGE Publishing, 2024)
Nowadays, in Benin, latrine construction by households highly depends on their financial contributions. However, empirical evidence shows that many households are unwilling to invest in adequate sanitation services. The study aims to determine the household's willingness to pay for improved sanitation services and the associated factors. The study population will include households lacking unimproved sanitation facilities. The household heads will be eligible for survey participation. We will perform a contingent valuation to determine households' willingness to pay for a Ventilated Improved Pit (VIP) latrine. Following a description of the surveyed population, we will assess willingness to pay using the ' doubleb ' command in Stata. Subsequently, we will conduct multivariate logistic regression to determine the factors associated with willingness to pay. The expected results will be: a description of the basic characteristics of households without improved sanitation services, an estimation of household willingness to pay for VIP latrines using the contingent valuation, and factors associated with household willingness to pay for VIP latrines. This study will contribute to the literature on household demand for improved sanitation services in Benin.